Determining the digital maturity index for assessing population health - Astafeva, O.V.; Borodina, O.A.; Perednih, L.V.; Ulyanova, S.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to provide a theoretical justification for the digital maturity index of the population in physical health management as an indicator of the demand for digital tools in maintaining a healthy lifestyle. Methods and structure of the study. A comprehensive approach was applied, including comparative analysis, analysis and synthesis methods, and modelling. Results and conclusions. The Digital Maturity Index for Managing Physical Health (DMIMPH) is a metric tool that quantifies the degree of integration of digital technologies into the management of human physical health based on the monitoring and assessment of biological parameters. DMIMPH allows assessing the level of digital maturity of the population using modern devices, health monitoring systems, and data exchange technologies. In this article, digital maturity is understood as the level of awareness, efficiency, and interest of a person in using modern technologies and technical devices. According to the authors, the digitalisation of health is the process of introducing and applying technologies and technical means into the daily life of an individual for the independent analysis, monitoring and control of health and physical condition. The article presents the main components of the human health digitalisation index, its calculation formula and a comparison with traditional health assessment scales, such as SF-36 and the Human Health Index (HHI). It is assumed that a high level of DMIMPH will, over time, contribute to the development of the accessibility and effectiveness of preventive medicine and telemedicine. Research into the Digital Maturity Index of Population Health Management (DMIMPH) opens up promising avenues for analysing the role of digital tools in modern medicine, as well as for developing new approaches to the digital maturity of patients in the context of telemedicine and preventive medicine.